Remote vehicle teleoperation through a haptic interface - Carrasquilla-Batista, Arys (2012)
Teleoperation allows human beings to carry out certain tasks in places far away, inaccessible or with hostile conditions for the presence of an operator. In this project a remote vehicle is teleoperated using a bluetooth wireless connection, to accomplish this an haptic interface (Novint Falcon) was used. The operator can give movement instructions to the vehicle and obtain sensations, according to the information received from the sensors connected to the system. The remote vehicle was a Lego Mindstorms with bluetooth communication capabilities, a touch sensor and ultrasonic sensor were included in order to perceive reflection of forces through the haptic interface. A USB adapter for bluetooth communication was added to a standard computer; a program in C++ is executed over this computer to control the haptic interface, send movement commands to the vehicle and receive sensor information to reproduce sensations to the operator.